Statistical analysis of resilience in an air transport network - Xu, Guoqiang; Zhang, Xuejun (Frontiers in Physics, 2022)
The resilience of an air transport network represents its ability to adapt and stay operational at the required level of safety and efficiency during the impact of various disturbances. These disturbances, which can compromise the resilience of a given air transport network, include inclement weather conditions, human-intended interruptions (such as terrorist attacks, air traffic controller strikes or pilots strikes) or unexpected mechanical failures (such as aircraft component breakdown or runway systems failures). The mitigating actions such as delaying, cancelling and rerouting affected flights aims at maintaining both the network’s resilience and safety at the acceptable level under given conditions. It is of great significance to understand and quantify resilience in the complex socio-technical air transport network, which has attracted extensive attentions. In this paper, statistical analysis of China air traffic data is applied to investigate the emergence of resilience in air transport network. The Granger Causality test is adopted to evaluate the causality relationship between different elements of a complex system. We construct the hourly delay propagation networks and analyze the resilience of air transport system through the evolution of delay propagation networks. The useful measurement metric of resilience is proposed and evolution patterns of generation and recovery of flight delays are also investigated. In addition, the relationship between initial delay, scheduled flights and resilience loss is studied to reveal further understanding of resilience in air transport system.